Analisis Potensi Pengembangan Wisata Berbasis Masyarakat di Kawasan Wisata Situ Cilangla, Kabupaten Tasikmalaya - Rosita, Mita; Mila Nadita; Aldin Alfariji; Astri Tresna Rahayu (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
Tourism plays a crucial role in increasing community participation while providing positive impacts on the economy, culture, and environment. This study aims to analyze the tourism development potential of Situ Cilangla in Raksasari Village, Taraju District, Tasikmalaya Regency. The qualitative method used was a SWOT analysis approach through interviews with managers, visitors, and the surrounding community. The results of the study indicate strengths in the form of scarcity of tourist attractions and free entry. Weaknesses include low visitor interest, suboptimal digital marketing, and limited land. Opportunities lie in the availability of good accommodation and services, while threats include the lack of tourist attractions and the existence of certain myths or beliefs. These findings can be used as a reference in formulating development strategies to increase the interest and awareness of Situ Cilangla among the public.